Qualitative Analysis of Parental Observations on Quality of Life in Australian Children with Down Syndrome. Issue 2 (February 2017) - Murphy, Nada; Epstein, Amy; Leonard, Helen; Davis, Elise; Reddihough, Dinah; Whitehouse, Andrew; Jacoby, Peter; Bourke, Jenny; Williams, Katrina; Downs, Jenny
ABSTRACT: Objective: There are many challenges to health, functioning, and participation for children with Down syndrome; yet, the quality-of-life (QOL) domains important for this group have never been clearly articulated. This study investigated parental observations to identify QOL domains in children with Down syndrome and determined whether domains differed between children and adolescents. Methods: The sample comprised 17 families whose child with Down syndrome was aged 6 to 18 years. Primary caregivers took part in semistructured telephone interviews to explore aspects of their child's life that were satisfying or challenging. Qualitative thematic analysis was implemented using a grounded theory framework to identify domains. The coded data set was divided into 2 groups (childhood and adolescence) at 3 age cut points to observe whether differences existed between the coded domains and domain elements: (1) 6 to 11 years with 12 to 18 years; (2) 6 to 13 years with 14 to 18 years; and (3) 6 to 15 years with 16 to 18 years. Results: Eleven domains were identified: physical health, behavior and emotion, personal value, communication, movement and physical activity, routines and predictability, independence and autonomy, social connectedness and relationships, variety of activities, nature and outdoors, and access to services. No differences in domains and domain elements were identified across childhood and adolescence. Conclusion: Our data form a preliminary framework from which to design investigations of the child's perspectives on life quality and suggest a range of necessary supports and services.